If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x) + 10 = 3x + 13 Remove parenthesis around (2x) 2 * 2x + 10 = 3x + 13 Multiply 2 * 2 4x + 10 = 3x + 13 Reorder the terms: 10 + 4x = 3x + 13 Reorder the terms: 10 + 4x = 13 + 3x Solving 10 + 4x = 13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 10 + 4x + -3x = 13 + 3x + -3x Combine like terms: 4x + -3x = 1x 10 + 1x = 13 + 3x + -3x Combine like terms: 3x + -3x = 0 10 + 1x = 13 + 0 10 + 1x = 13 Add '-10' to each side of the equation. 10 + -10 + 1x = 13 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 13 + -10 1x = 13 + -10 Combine like terms: 13 + -10 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| -5x+2y=11 | | -10x=-10 | | x+8=2x-10 | | 27x=-1 | | 14=2x-9 | | 32=2x-10 | | 20u+18v= | | 5y^2-33y-14=0 | | -8x=-2 | | x^2-2x-36=0 | | 0.25x-14.8= | | 10x=42 | | 9x=-8 | | v(10)-v(3)= | | -6X+4=7X+121 | | 5x-7(0)=-18 | | k=0 | | 5(0)-7y=-18 | | 7X+1=121-5X | | (q^2+5q+4)(q^2-1)+q^3-q=2q+2q^2-2 | | -4X+10=21+7X | | 3x-6(0)=-7 | | 3(0)-6y=-7 | | 2=-1x+45-8 | | 2=-1x+45 | | 2=-1x+9 | | 2=-1x+4 | | 3-4X=-2X+17 | | -2-8x=0 | | 4X+3=7X-12 | | -1-8x=0 | | w^2+12w+40=0 |